Low-heat-generation fatigue-resistant phase-change rubber sole and preparation method thereof

By using rubbers, such as high vinyl polybutadiene, carboxy-soluble polystyrene, trans-1,4-polyisoprene, and nanomicrocapsule phase change materials and carboxy-based nano-sea carbon black in rubber soles, the solution is solved The problem of deteriorating heat wear resistance caused by high-intensity exercise by rubber soles has achieved the improvement of low heat generation and high thermal conductivity, meeting the needs of high-intensity exercise.

CN119219997AActive Publication Date: 2024-12-31ANTA (CHINA) CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411746851.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2024-12-31
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

The existing rubber soles have deteriorated heat wear and fatigue resistance due to heat generation during high-strength exercise, which affects the service life, and the industry has little research on this issue.

Method used

Use high vinyl polybutadiene rubber, carboxy-soluble polystyrene butadiene rubber, trans-1,4-polyisoprene rubber, methyl methacrylate grafted natural rubber and other rubbers, and match with nano double capsule micro The capsule phase change material and carboxylated nano-sea carbon black form chemical bonds and excellent compatibility, reduce friction heat and interface thermal resistance, and improve thermal conductivity.

Benefits of technology

It realizes low heat generation and fatigue-resistant phase change rubber sole with low heat generation and high thermal conductivity, maintains thermal wear resistance and fatigue resistance under dynamic movement, meets the needs of high-intensity motion scenarios, and compresses fatigue heat generation ≤15℃ , Thermal conductivity is ≥0.6W/mK, and the DIN thermal wear resistance is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

According to the low-heat-generation fatigue-resistant phase-change rubber shoe sole and the preparation method thereof, high vinyl polybutadiene rubber, carboxyl solution polymerized styrene-butadiene rubber, trans-1, 4-polyisoprene rubber and methyl methacrylate grafted natural rubber are adopted, and a nano double-capsule microcapsule phase-change material and carboxyl nano white carbon black are matched, so that the low-heat-generation fatigue-resistant phase-change rubber shoe sole is prepared. The nano microcapsule phase change material is added into the rubber matrix, so that firm chemical bonds and excellent compatibility are formed among the nano microcapsule phase change material, the reinforcing agent, the rubber matrix and the like, the friction heat and interface thermal resistance among the components are effectively reduced, and the effects of low heat generation and high thermal conductivity are favorably maintained. The compression fatigue heat generation is less than or equal to 15 DEG C, the heat conductivity coefficient is greater than or equal to 0.6 (W / mK), the DIN wear resistance (normal temperature) is less than or equal to 60mm < 3 >, the DIN thermal wear resistance (55 DEG C) is less than or equal to 80mm < 3 >, the density is 1.1-1.2 g / cm < 3 >, the hardness is 55-65A, the tensile strength is greater than or equal to 20MPa, the right-angle tear strength is greater than or equal to 30N / mm, and the dynamic slip resistance is greater than or equal to 0.6.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of soles, and in particular relates to a low-heat-generation and fatigue-resistant phase-change rubber sole and a preparation method thereof. Background Art

[0002] At present, the performance of rubber soles mainly includes softness, wear resistance, anti-slip, yellowing resistance, aging resistance, ozone resistance, etc. The wear resistance emphasized here usually refers to normal temperature wear resistance (23°C). When consumers wear sports shoes for high-intensity exercise, the rubber outsole in direct contact with the ground will produce large deformation and heat due to the violent movement, causing the internal temperature of the rubber to rise and the wear resistance to deteriorate. Therefore, it is often the case that rubber soles with excellent normal temperature wear resistance are not wear-resistant during actual wearing. This is mainly due to the heat generated inside the rubber, which causes the thermal wear resistance and fatigue resistance of the sole to deteriorate, and often also affects the service life of the shoes. Therefore, thermal wear resistance is more necessary during actual exercise.

[0003] At present, there are few studies on the heat generation of rubber soles in the industry. Most rubber researchers only focus on reducing the heat generation of rubber tires. The heat generation of rubber tires is mainly caused by filler-filler friction, filler-rubber friction and rubber-rubber friction. Therefore, how to reduce the internal heat generation of rubber composites and enhance the interaction between fillers and the matrix interface is the key to achieving high thermal conductivity and low heat generation performance of rubber tires. At present, there are three main measures to reduce the heat generation of rubber tires: one is to select low-heat-generating rubber varieties and fillers and other compounding agents; the second is to improve the heat resistance of tire rubber, which is mainly achieved by reasonably selecting vulcanization systems and antioxidants; the third is to improve the thermal conductivity of tire rubber, which is generally achieved by selecting suitable thermal conductive fillers. However, the above technical solutions all have certain shortcomings, so how to reduce the heat generation of rubber soles has practical research significance. Summary of the invention

[0004] In view of this, the purpose of the present invention is to provide a low heat generation and fatigue-resistant phase change rubber sole and a preparation method thereof. The rubber sole has excellent low heat generation and high thermal conductivity, maintains the thermal wear resistance and fatigue resistance of the rubber sole under dynamic movement, and meets the performance requirements of consumers for high-intensity sports scenes.

[0005] The present invention provides a low heat generation and fatigue resistant phase change rubber sole, which comprises the following raw materials in parts by mass: 40-50 parts of high vinyl polybutadiene rubber, 10-20 parts of carboxyl soluble styrene butadiene rubber, 10-20 parts of trans-1,4-polyisoprene rubber, 20-30 parts of methyl methacrylate grafted natural rubber, 5-10 parts of nano double capsule microcapsule phase change material, 25-35 parts of carboxyl nano white carbon black, 2-4 parts of hydrogenated petroleum resin, 3-5 parts of softening oil, 2-3.5 parts of vulcanization activator, 1.5-2.5 parts of polyethylene glycol, 2-3 parts of hydroxy silane coupling agent, 0.5-1.0 parts of stearic acid, 0.4-0.8 parts of antioxidant, 0.5-1.0 parts of antioxidant, 1.5-2.5 parts of microcrystalline wax, 0.5-1 parts of nano alumina, 2-2.5 parts of sulfur, 1-1.5 parts of accelerator DM, 0.5-0.8 parts of accelerator D and accelerator TS 0.05~0.1 portion.

[0006] Preferably, the high vinyl polybutadiene rubber has a vinyl content of 65-75% by mass and a Mooney viscosity of 55±5 (ML1+4@100°C).

[0007] Preferably, the carboxyl solution-polymerized styrene-butadiene rubber has a carboxyl molar content of 5-10%, a styrene content of 20-30%, and a Mooney viscosity of 45±5 (ML1+4@100°C).

[0008] Preferably, the trans molar content of the trans-1,4-polyisoprene rubber is ≥90%, and the Mooney viscosity is 75±5 (ML1+4@100°C).

[0009] Preferably, the methyl methacrylate grafted natural rubber has a methyl methacrylate molar content of 10-15% and a Mooney viscosity of 80±5 (ML1+4@100°C).

[0010] Preferably, the particle size of the nano-microcapsule phase change material is 200-500 nm, the phase change temperature is 28±2° C., the thermal conductivity is 1.5-3 w / (mK), and the endothermic enthalpy is 170±20 J / g.

[0011] Preferably, the hydrogenated petroleum resin is selected from one or more of hydrogenated C5 petroleum resin, hydrogenated C9 petroleum resin and hydrogenated cyclopentadiene petroleum resin; The softening oil is selected from paraffin oil and / or naphthenic oil; The vulcanization activator is selected from a compound of active zinc oxide and zinc stearate; The molecular weight of the polyethylene glycol is 3600-4200; The hydroxy silane coupling agent is cyclohexylaminopropyltrimethoxysilane; The antioxidant is an amine antioxidant and / or a phenolic antioxidant; The antioxidant is selected from phosphite antioxidants and / or phenol antioxidants; The microcrystalline wax is selected from C25-C30 microcrystalline wax; The particle size of the nano-alumina is 20-50 nm, and the specific surface area is ≥230 m 2 / g.

[0012] Preferably, the compression fatigue heat generation of the low heat generation and fatigue resistance phase change rubber sole is ≤15°C, the thermal conductivity is ≥0.6 (W / mK), and the DIN wear resistance is ≤60mm at room temperature. 3 , DIN thermal wear resistance ≤80mm at 55℃ 3 .

[0013] The present invention provides a method for preparing the low heat generation and fatigue resistant phase change rubber sole described in the above technical solution, comprising the following steps: a) Mix high vinyl polybutadiene rubber, carboxyl soluble styrene butadiene rubber, trans-1,4-polyisoprene rubber, methyl methacrylate grafted natural rubber, nano double capsule microcapsule phase change material, hydrogenated petroleum resin, softening oil, carboxyl nano white carbon black, and hydroxy silane coupling agent, knead, heat to 100-120°C, and pour out the rubber material; b) Sheeting the rubber material into a sheet with a thickness of 1±0.2 cm and leaving it for 5 to 8 hours; c) Mix the rubber sheet with the additives except accelerator and sulfur again, heat it to 100-120℃, and pour out the rubber; d) After rolling the rubber material for 5 to 10 times, add accelerator DM, accelerator D, accelerator TS and sulfur, and sheet out to a thickness of 0.5±0.1 cm; e) vulcanizing the 0.5±0.1 cm thick sheet to obtain a low heat buildup and fatigue resistant phase change rubber sole.

[0014] Preferably, the mixing time in step a) and step c) is 8 to 10 minutes; In step e), the vulcanization temperature is 163±3°C and the time is 280±20s.

[0015] The present invention aims to prepare a phase change rubber sole with low heat generation and fatigue resistance. By adopting four types of rubbers such as high vinyl polybutadiene rubber with low heat generation, carboxyl soluble styrene butadiene rubber, trans-1,4-polyisoprene rubber, and methyl methacrylate grafted natural rubber, and matching them with a double-capsule multifunctional nano-microcapsule phase change material and a functional reinforcing agent carboxyl nano-silica, a strong chemical bond and excellent compatibility are formed between the nano-microcapsule phase change material, the reinforcing agent, and the rubber matrix, effectively reducing the friction heat and interfacial thermal resistance between the components, which is conducive to maintaining low heat generation and high thermal conductivity. The experimental results show that the compression fatigue heat generation of the low heat generation and fatigue resistance phase change rubber sole prepared by the present invention is ≤15°C, the thermal conductivity is ≥0.6 (W / mK), and the DIN wear resistance (normal temperature) is ≤60mm 3 , DIN heat wear resistance (55℃) ≤80mm 3 , density 1.1~1.2g / cm 3 , hardness 55~65A, tensile strength ≥20MPa, right-angle tear strength ≥30 N / mm, dynamic anti-slip ≥0.6 and other excellent rubber soles. The heat generation value is ≤15℃, and the difference between the heat wear resistance at 55℃ and the DIN wear resistance at room temperature is less than 19mm 3 , compared with the existing low heat generation rubber, it has a significant breakthrough in data. DETAILED DESCRIPTION

[0016] The present invention provides a low heat generation and fatigue resistant phase change rubber sole, which comprises the following raw materials in parts by mass: 40-50 parts of high vinyl polybutadiene rubber, 10-20 parts of carboxyl soluble styrene butadiene rubber, 10-20 parts of trans-1,4-polyisoprene rubber, 20-30 parts of methyl methacrylate grafted natural rubber, 5-10 parts of nano double capsule microcapsule phase change material, 25-35 parts of carboxyl nano white carbon black, 2-4 parts of hydrogenated petroleum resin, 3-5 parts of softening oil, 2-3.5 parts of vulcanization activator, 1.5-2.5 parts of polyethylene glycol, 2-3 parts of hydroxy silane coupling agent, 0.5-1.0 parts of stearic acid, 0.4-0.8 parts of antioxidant, 0.5-1.0 parts of antioxidant, 1.5-2.5 parts of microcrystalline wax, 0.5-1 parts of nano alumina, 2-2.5 parts of sulfur, 1-1.5 parts of accelerator DM, 0.5-0.8 parts of accelerator D and accelerator TS 0.05~0.1 portion.

[0017] The raw materials for preparing the low heat generation and fatigue resistant phase change rubber sole provided by the present invention include 40 to 50 parts of high vinyl polybutadiene rubber, and the specific amount is 40 parts, 41 parts, 42 parts, 43 parts, 44 parts, 45 parts, 46 parts, 47 parts, 48 ​​parts, 49 parts or 50 parts. In the present invention, the high vinyl polybutadiene rubber is also called 1,2-polybutadiene rubber; the vinyl mass content of the high vinyl polybutadiene rubber is 65 to 75%, and the Mooney viscosity is 55±5 (ML1+4@100°C); the vinyl polybutadiene rubber with the above vinyl content not only has low heat generation and anti-slip properties, but also maintains the wear resistance of butadiene rubber.

[0018] The raw materials for preparing the low heat generation and fatigue resistant phase change rubber sole provided by the present invention include 10 to 20 parts of carboxyl solution polymerized styrene butadiene rubber, and the specific amount is 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts or 20 parts. The carboxyl solution polymerized styrene butadiene rubber has a carboxyl molar content of 5 to 10%, a styrene content of 20 to 30%, and a Mooney viscosity of 45±5 (ML1+4@100°C). The carboxyl-modified solution polymerized styrene butadiene rubber improves the polarity of the solution polymerized styrene butadiene rubber, and has better compatibility when blended with polar rubber and polar reinforcing agents, thereby better exerting its own performance.

[0019] The raw materials for preparing the low heat generation and fatigue resistant phase change rubber sole provided by the present invention include 10 to 20 parts of trans-1,4-polyisoprene rubber, and the specific amount is 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts or 20 parts. The trans molar content of the trans-1,4-polyisoprene rubber is ≥90%, and the Mooney viscosity is 75±5 (ML1+4@100°C); the trans molecular structure and highly ordered molecular chain contained in the trans-1,4-polyisoprene rubber with the above trans content and Mooney viscosity give it excellent physical and mechanical properties, and the friction within the molecular chain of TPI is small, and it has low heat generation characteristics and dynamic fatigue performance after being fully cross-linked.

[0020] The raw materials for preparing the low heat generation and fatigue resistant phase change rubber sole provided by the present invention include 20 to 30 parts of methyl methacrylate grafted natural rubber, and the specific amount is 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts or 30 parts. The methyl methacrylate grafted natural rubber has a methyl methacrylate molar content of 10 to 15% and a Mooney viscosity of 80±5 (ML1+4@100°C). Natural rubber is non-polar and has poor compatibility with polar white carbon black. By modifying the natural rubber with methyl methacrylate, some double bonds in the molecular chain form carboxyl groups and ester groups, which increases its polarity and increases the intermolecular force, resulting in a decrease in the flexibility of the molecular chain and a weakening of the molecular thermal motion. Therefore, it has lower heat generation, and better compatibility when blended with polar rubber and polar reinforcing agents, so as to better exert its own performance.

[0021] The present invention adopts four kinds of rubbers, namely, high vinyl polybutadiene rubber with low heat generation, carboxyl soluble polystyrene butadiene rubber, trans-1,4-polyisoprene rubber, and methyl methacrylate grafted natural rubber, and matches them with a dual-capsule multifunctional nano-microcapsule phase change material and a functional reinforcing agent, carboxyl nano-white carbon black, so that a strong chemical bond and excellent compatibility are formed among the nano-microcapsule phase change material, the reinforcing agent, and the rubber matrix, effectively reducing the friction heat and interface thermal resistance between the components, which is beneficial to reducing the low heat generation of the rubber and improving the thermal conductivity. Among them, ① high vinyl polybutadiene rubber contributes to low heat generation, anti-slip and wear resistance due to the high content of vinyl in the side chain; ② carboxyl soluble styrene butadiene rubber slows down the movement ability of styrene butadiene rubber molecular chain due to the presence of polar groups, which is beneficial to reduce the movement friction heat generation of the rubber itself. The carboxyl group can form a strong cross-linking network in the rubber material with the hydroxyl group of the microcapsule phase change material shell in the form of ionic bonds or hydrogen bonds, and weakens the aggregation ability of the phase change material, improves the dispersion of the phase change material in the rubber matrix, reduces the friction between the rubber matrix and the phase change material, and reduces heat generation; ③ trans-1,4-polyisoprene rubber (TPI) has a unique trans molecular structure and highly ordered molecular chain, so the friction within the molecular chain is small, and after cross-linking, it has low heat generation characteristics and good dynamic fatigue performance; ④ methyl methacrylate grafted natural rubber: after natural rubber is grafted with methyl methacrylate, some double bonds in the molecular chain form carboxyl and ester groups, which increases its polarity and the intermolecular force, resulting in a decrease in the flexibility of the molecular chain and a weakening of the molecular thermal motion, so it has a lower heat generation.

[0022] The raw materials for preparing the low heat generation and fatigue resistance phase change rubber sole provided by the present invention include 5 to 10 parts of nano double capsule microcapsule phase change material, and the specific amount is 5 parts, 5.5 parts, 6 parts, 6.5 parts, 7 parts, 7.5 parts, 8 parts, 8.5 parts, 9 parts, 9.5 parts or 10 parts. The particle size of the nano microcapsule phase change material is 200 to 500nm, the phase change temperature is 28±2℃, the thermal conductivity is 1.5 to 3 w / (mK), and the endothermic enthalpy value is 170±20 J / g. The nanometer double capsule microcapsule phase change material of the present invention, on the one hand, significantly increases the specific surface area of ​​the microcapsule phase change material as the size of the phase change microcapsule is nanometerized, improves the dispersibility of the microcapsule phase change material in the rubber matrix, and improves the contact area and coverage of the microcapsule phase change material in the rubber matrix, greatly improving the effective utilization rate and thermal conductivity of the microcapsule phase change material; on the other hand, the inner layer of the double capsule phase change microcapsule adopts polyurethane, an organic polymer material with excellent flexibility, and the outer layer adopts hydroxyl silica with high heat resistance and high stability, forming an inorganic / organic composite hybrid double capsule structure, which well maintains the endothermic enthalpy value and thermal conductivity. Moreover, the hydroxyl silica in the outer layer can form ionic bonds or hydrogen bonds with the carboxyl-soluble styrene-butadiene rubber in the matrix rubber and the carboxyl in the methyl methacrylate grafted natural rubber, forming a strong cross-linking network in the rubber material; on the other hand, the hydroxyl silica and the reinforcing agent carboxyl nano-white carbon black are both silica, which is conducive to achieving molecular compatibility, and the hydroxyl and carboxyl groups can also form an ionic bond or hydrogen bond reinforced filler network. The nano-microcapsule phase change material, the reinforcing agent and the rubber matrix in the present invention form a strong chemical bond and excellent compatibility, which effectively reduces the friction heat and interface thermal resistance between the components, and is beneficial to reducing heat generation and improving thermal conductivity.

[0023] The raw materials for preparing the low heat generation and fatigue resistant phase change rubber sole provided by the present invention include 25 to 35 parts of carboxyl nano-white carbon black, and the specific amount is 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, 30 parts, 31 parts, 32 parts, 33 parts, 34 parts or 35 parts. The present invention prepares the carboxyl nano-white carbon black by modifying the nano-white carbon black with methacrylic acid; on the one hand, methacrylic acid increases the polarity of the white carbon black, and has better compatibility with polar matrix rubbers such as carboxyl solution-polymerized styrene-butadiene rubber and methyl methacrylate grafted natural rubber; the nano-scale size increases the specific surface area of ​​the carboxyl white carbon black, improves the dispersibility of the white carbon black in the rubber matrix and the contact area and coverage in the rubber matrix, greatly enhances the interface effect with the rubber matrix, exerts a better reinforcement effect, and improves the wear resistance, tensile strength and tear strength of the rubber sole; and reduces the friction between the white carbon black and the rubber matrix, which is conducive to reducing the dynamic heat generation of the rubber sole. On the other hand, the carboxyl groups on its surface form a strong chemical bond with the hydroxyl silica in the shell of the nano-microcapsule phase change material, which is beneficial to improving the compatibility and interfacial effect between the two.

[0024] The raw materials for preparing the low heat generation and fatigue resistant phase change rubber sole provided by the present invention include 2 to 4 parts of hydrogenated petroleum resin, and the specific amount is 2 parts, 2.5 parts, 3.0 parts, 3.5 parts or 4.0 parts. The hydrogenated petroleum resin is selected from one or more of hydrogenated C5 petroleum resin, hydrogenated C9 petroleum resin and hydrogenated cyclopentadiene petroleum resin; preferably hydrogenated C9 petroleum resin.

[0025] The raw materials for preparing the low heat generation and fatigue resistant phase change rubber sole provided by the present invention include 3 to 5 parts of softening oil, and the specific amount is 3 parts, 3.1 parts, 3.2 parts, 3.3 parts, 3.4 parts, 3.5 parts, 3.6 parts, 3.7 parts, 3.8 parts, 3.9 parts or 4.0 parts. The softening oil is selected from paraffin oil and / or cyclohexane oil, and is preferably paraffin oil.

[0026] The raw materials for preparing the low heat generation and fatigue resistant phase change rubber sole provided by the present invention include 2 to 3.5 parts of a vulcanization activator, and the specific amount is 2.0 parts, 2.1 parts, 2.2 parts, 2.3 parts, 2.4 parts, 2.5 parts, 2.6 parts, 2.7 parts, 2.8 parts, 2.9 parts, 3.0 parts, 3.1 parts, 3.2 parts, 3.3 parts, 3.4 parts or 3.5 parts. The vulcanization activator is selected from a compound of active zinc oxide and zinc stearate; preferably, a compound of active zinc oxide and zinc stearate in a mass ratio of 2:1.

[0027] The raw materials for preparing the low heat generation and fatigue resistant phase change rubber sole provided by the present invention include 1.5 to 2.5 parts of polyethylene glycol, and the specific amount is 1.5 parts, 1.6 parts, 1.7 parts, 1.8 parts, 1.9 parts, 2.0 parts, 2.1 parts, 2.2 parts, 2.3 parts, 2.4 parts or 2.5 parts. The molecular weight of the polyethylene glycol is 3600 to 4200.

[0028] The low heat generation and fatigue resistance phase change rubber sole provided by the present invention comprises 2 to 3 parts of hydroxy silane coupling agent, and the specific amount is 2 parts, 2.1 parts, 2.2 parts, 2.3 parts, 2.4 parts, 2.5 parts, 2.6 parts, 2.7 parts, 2.8 parts, 2.9 parts, or 3.0 parts. In the present invention, the hydroxy silane coupling agent can effectively couple the polar material with the non-polar material. The hydroxy silane coupling agent is 3-aminopropyl trihydroxy silane.

[0029] The raw materials for preparing the low heat generation and fatigue resistance phase change rubber sole provided by the present invention include 0.5 to 1.0 parts of stearic acid, and the specific amount is 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts or 1.0 parts. The stearic acid has a lubricating effect and is a white waxy particle with a density of 0.84g / cm 3 , melting point is 67~72℃.

[0030] The raw materials for preparing the low heat generation and fatigue resistant phase change rubber sole provided by the present invention include 0.4 to 0.8 parts of antioxidant, and the specific amount is 0.4 parts, 0.45 parts, 0.50 parts, 0.55 parts, 0.60 parts, 0.65 parts, 0.70 parts, 0.75 parts or 0.8 parts. The antioxidant is an amine antioxidant and / or a phenolic antioxidant; the phenolic antioxidant is preferably butylated hydroxytoluene.

[0031] The raw materials for preparing the low heat generation and fatigue resistant phase change rubber sole provided by the present invention include 0.5 to 1.0 parts of antioxidants, and the specific amount is 0.5 parts, 0.55 parts, 0.60 parts, 0.65 parts, 0.70 parts, 0.75 parts, 0.80 parts, 0.85 parts, 0.90 parts, 0.95 parts or 1.0 parts. The antioxidant is selected from phosphite antioxidants and / or phenol antioxidants; the phenol antioxidant is preferably butylated hydroxytoluene.

[0032] The raw materials for preparing the low heat generation and fatigue resistant phase change rubber sole provided by the present invention include 1.5 to 2.5 parts of microcrystalline wax, and the specific amount is 1.5 parts, 1.6 parts, 1.7 parts, 1.8 parts, 1.9 parts, 2.0 parts, 2.1 parts, 2.2 parts, 2.3 parts, 2.4 parts or 2.5 parts. The microcrystalline wax in the present invention has an anti-cracking protective effect. The microcrystalline wax is selected from C25 to C30 microcrystalline wax.

[0033] The raw materials for preparing the low heat generation and fatigue resistance phase change rubber sole provided by the present invention include 0.5 to 1 part of nano-alumina, and the specific amount is 0.5 part, 0.55 part, 0.60 part, 0.65 part, 0.70 part, 0.75 part, 0.80 part, 0.85 part, 0.90 part, 0.95 part or 1.0 part. The particle size of the nano-alumina is 20 to 50 nm, and the specific surface area is ≥230 m 2 / g. The nano-alumina described in the present invention can improve the heat resistance and fatigue resistance of rubber.

[0034] The low heat generation and fatigue resistant phase change rubber sole provided by the present invention comprises 2 to 2.5 parts of sulfur, and the specific amount is 2.0 parts, 2.05 parts, 2.1 parts, 2.15 parts, 2.2 parts, 2.25 parts, 2.3 parts, 2.35 parts, 2.4 parts, 2.45 parts or 2.5 parts. The sulfur is a crosslinking agent; the insoluble element sulfur content in the sulfur is ≥70%, and the oil-filled content is 19 to 21%.

[0035] The raw materials for preparing the low heat generation and fatigue resistant phase change rubber sole provided by the present invention include 1-1.5 parts of accelerator DM, 0.5-0.8 parts of accelerator D and 0.05-0.1 parts of accelerator TS, wherein the accelerator is specifically one or more of thiazoles, thiurams and guanidines. In a specific embodiment, the accelerator dosage is 1.2 parts of accelerator DM, 0.6 parts of accelerator D and 0.075 parts of accelerator TS.

[0036] The low heat generation and fatigue resistance phase change rubber sole provided by the present invention has a compression fatigue heat generation of ≤15°C, a thermal conductivity of ≥0.6 (W / mK), and a DIN wear resistance of ≤60mm at room temperature. 3 , DIN thermal wear resistance ≤80mm at 55℃ 3 .

[0037] The present invention provides a method for preparing the low heat generation and fatigue resistant phase change rubber sole described in the above technical solution, comprising the following steps: a) Mix high vinyl polybutadiene rubber, carboxyl soluble styrene butadiene rubber, trans-1,4-polyisoprene rubber, methyl methacrylate grafted natural rubber, nano double capsule microcapsule phase change material, hydrogenated petroleum resin, softening oil, carboxyl nano white carbon black, and hydroxy silane coupling agent, knead, heat to 100-120°C, and pour out the rubber material; b) Sheeting the rubber material into a sheet with a thickness of 1±0.2 cm and leaving it for 5 to 8 hours; c) Mix the rubber sheet after storage with the auxiliary agents except the accelerator and the cross-linking agent, heat it to 100-120℃, and pour out the rubber; d) After rolling the rubber material for 5 to 10 times, add accelerator DM, accelerator D, accelerator TS and sulfur, and sheet out to a thickness of 0.5±0.1 cm; e) vulcanizing the 0.5±0.1 cm thick sheet to obtain a low heat buildup and fatigue resistant phase change rubber sole.

[0038] The invention mixes the parked film again with auxiliary agents except the accelerator and the crosslinking agent. Specifically, the invention mixes the parked film with a vulcanizing activator, polyethylene glycol, stearic acid, an antioxidant, an antioxidant, microcrystalline wax and nano-alumina.

[0039] In the present invention, the mixing time in step a) and step c) is 8 to 10 minutes; the vulcanization temperature in step e) is 163±3° C. and the time is 280±20 seconds.

[0040] The present invention is the first to use thermal wear resistance indicators to characterize the wear resistance of rubber soles under intense exercise conditions. Compared with the industry's use of only room temperature DIN wear resistance for characterization, it can more scientifically and intuitively demonstrate the fatigue resistance of rubber soles under dynamic exercise, which is a first in the industry.

[0041] In order to further illustrate the present invention, a low heat build-up and fatigue-resistant phase change rubber sole and a preparation method thereof provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0042] Examples and Comparative Examples See Table 1, Table 2 and Table 3 for the types and amounts of each raw material: Pour the base rubber, hydrogenated petroleum resin, carboxyl nano-white carbon black, hydroxy silane coupling agent and softening oil into the internal mixer, start the internal mixer, mix for 8-10 minutes to fully mix the rubber and petroleum resin. When the temperature of the internal mixer rises to 100-120℃, pour out the mixed rubber; Put the mixed rubber into an open mixing mill, roll it 8 times continuously, and form it into a thin sheet with a thickness of 1 cm. Leave it for 5 hours for later use.

[0043] After being parked for 5 hours, pour the mixed rubber into the internal mixer again, and pour other additives except the accelerator and crosslinking agent sulfur into the internal mixer, mix for 10 minutes, and pour out the mixed rubber when the temperature of the internal mixer rises to 100℃; Pour the mixed rubber into an open mill, roll it 8 times continuously, add accelerator and cross-linking agent sulfur, and roll it into a 0.5 cm thick sheet; Cut a 0.5 cm thick sheet into the size required by the mold, put it into the sole mold, and vulcanize it for 280±20 seconds using a flat vulcanizer at a temperature of 163±3°C, and take out the vulcanized rubber sole.

[0044] Table 1 Raw material composition of Examples 1 to 6 Table 2 Raw material composition of Examples 7 to 13 Table 3 Raw material composition of Comparative Examples 1 to 10 It can be seen from Tables 1 to 3 that: (1) From the comparison data of Examples 1 to 6 and Comparative Examples 6, 7 and 8, it can be seen that when the addition amount of the nano-double capsule microcapsule phase change material is 5 to 10 parts, the compression fatigue heat generation of the rubber sole decreases with the increase in the addition amount of the nano-double capsule microcapsule phase change material, the thermal conductivity increases with the increase in the addition amount of the nano-double capsule microcapsule phase change material, and the gap between the 55°C thermal wear resistance and the room temperature wear resistance gradually decreases with the increase in the addition amount of the nano-double capsule microcapsule phase change material. When the addition amount is 5 parts, the improvement effect is more obvious than that of 4 parts, but as the addition amount reaches 8 to 10 parts, the improvement of the wear resistance and anti-slip performance slows down. When the addition amount reaches 12 parts, there is little difference compared to the addition amount of 10 parts. This is mainly because: the phase change temperature of the nano double capsule microcapsule phase change material is about 28°C, which is conducive to heat conduction and reducing the heat generated by dynamic compression of rubber. In addition, the hydroxyl silica in the outer layer can form ionic bonds or hydrogen bonds with the carboxyl-soluble styrene-butadiene rubber in the matrix rubber and the carboxyl in the methyl methacrylate grafted natural rubber, thereby forming a strong cross-linking network locally in the rubber material; on the other hand, hydroxyl silica and the reinforcing agent carboxyl silica are both silica, which is conducive to achieving molecular-level compatibility and can also form an ionic bond or hydrogen bond reinforced filler network, effectively reducing the friction heat and interface thermal resistance between the components, which is conducive to reducing heat generation and high thermal conductivity.

[0045] (2) From the comparative data of Examples 4 and 7 to 13, it can be seen that when the addition amount of the fixed nano double capsule microcapsule phase change material is 8 parts, 40 to 50 parts of high vinyl polybutadiene rubber, 10 to 20 parts of carboxyl soluble styrene butadiene rubber, 10 to 20 parts of trans-1,4-polyisoprene rubber, 20 to 30 parts of methyl methacrylate grafted natural rubber, and 25 to 35 parts of carboxyl nano-silica can all be prepared with compression fatigue heat generation ≤15°C, thermal conductivity ≥0.6 (W / mK), and DIN wear resistance (normal temperature) ≤60mm 3 , DIN heat wear resistance (55℃) ≤80mm 3 , density 1.1~1.2g / cm 3 , hardness 55~65A, tensile strength ≥20MPa, right-angle tear strength ≥30 N / mm, dynamic anti-slip ≥0.6, and a rubber outsole with excellent properties. The greater the amount of high vinyl polybutadiene rubber added, the better the wear resistance of the rubber sole; the greater the amount of carboxyl solution polystyrene butadiene rubber added, the better the dynamic wet slip of the rubber sole; the greater the amount of trans-1,4-polyisoprene rubber added, the lower the compression fatigue heat generation of the rubber sole; the greater the amount of methyl methacrylate grafted natural rubber added, the better the tensile / tear mechanical properties of the rubber sole; the greater the amount of carboxyl nano-silica added, the higher the hardness of the sole, and the better the wear resistance, tensile, tearing and other properties.

[0046] (3) From the comparison data of Comparative Example 1 and Example 4, it can be seen that when the high vinyl polybutadiene rubber in the formula is replaced with nickel-based cis-butadiene rubber, since the nickel-based cis-butadiene rubber has a high cis structure and the side chain does not contain vinyl, the molecular chain moves freely, resulting in increased compression fatigue heat generation, decreased thermal conductivity of the sole, and an increase in the gap between 55°C thermal wear resistance and room temperature wear resistance, and a decrease in dynamic anti-slip performance.

[0047] (4) From the comparison data of Comparative Example 2 and Example 4, it can be seen that when the carboxyl solution polymerized styrene butadiene rubber in the formula is replaced with styrene butadiene rubber, since styrene butadiene rubber is non-polar, the molecular chain movement ability is stronger than that of carboxyl solution polymerized styrene butadiene rubber, which is not conducive to reducing the movement friction heat generated by the styrene butadiene rubber itself, and the difference in the force between the non-polar styrene butadiene rubber and the polar microcapsule phase change material and carboxyl nano-silica is not conducive to the dispersion and reinforcement of the phase change material and silica, resulting in increased compression fatigue heat generation, decreased thermal conductivity, and an increase in the gap between 55°C thermal wear resistance and room temperature wear resistance, and a decrease in dynamic anti-skid performance. Therefore, this application selects carboxyl solution polymerized styrene butadiene rubber to reduce heat generation and improve dynamic wet skid performance.

[0048] (5) From the comparison data of Comparative Example 3 and Example 4, it can be seen that when the trans-1,4-polyisoprene rubber in the formula is replaced with isoprene rubber, the molecular chains of the cis molecular structure of isoprene rubber move freely, resulting in high compression fatigue heat generation, and the gap between 55°C thermal wear resistance and room temperature wear resistance increases, and the dynamic fatigue performance is poor. Therefore, the patent of the present invention selects trans-1,4-polyisoprene rubber to reduce heat generation and improve fatigue resistance.

[0049] (6) From the comparison data of Comparative Example 4 and Example 4, it can be seen that: when the methyl methacrylate grafted natural rubber in the formula is replaced with natural rubber, since natural rubber is non-polar, the molecular chain movement ability is stronger than that of methyl methacrylate grafted natural rubber, which is not conducive to reducing the movement friction heat generated by the styrene-butadiene rubber itself. In addition, the difference in the interaction force between the non-polar natural rubber and the polar microcapsule phase change material and carboxyl nano-silica is not conducive to the dispersion and reinforcement of the phase change material and silica, resulting in increased compression fatigue heat generation, decreased thermal conductivity, and an increase in the gap between 55°C thermal wear resistance and room temperature wear resistance, and a decrease in dynamic anti-slip performance.

[0050] (7) From the comparison data of Comparative Example 5 and Example 4, it can be seen that when the carboxyl nano-silica in the formula is replaced with ordinary silica, the ordinary silica has poor compatibility with carboxyl solution-polymerized styrene-butadiene rubber and methyl methacrylate grafted natural rubber, and the interfacial interaction force with the microcapsule phase change material is low, which is not conducive to the dispersion of silica, increases the friction between silica and the components, and leads to increased compression fatigue heat generation and decreased thermal conductivity / tensile strength / right-angle tear strength.

[0051] (8) From the comparison data of Comparative Example 9 and Example 4, it can be seen that when the four low heat generation rubbers of the present application are not used, but conventional cis-1,1-butadiene rubber, styrene-butadiene rubber, isoprene rubber, natural rubber, etc. are used, although the amount of nano-microcapsule phase change material is maintained, the compression fatigue heat generation is significantly increased (greater than 22°C), the thermal conductivity is significantly decreased (less than 0.3W / mK), and the difference between the 55°C thermal wear resistance and the room temperature wear resistance is significantly increased (greater than 22mm 3 ), and the tensile strength and tear strength decreased significantly. This shows that the use of a low-heat-generating rubber matrix is ​​beneficial to reducing the compression fatigue heat generation and thermal conductivity of the rubber sole, and improving the dynamic fatigue performance of the sole.

[0052] (9) From the comparison data of Comparative Example 10 and Example 4, it can be seen that when the four low heat generation rubbers and nano double capsule microcapsule phase change materials of the present invention are removed, the compression fatigue heat generation of the rubber sole increases significantly (greater than 25°C), the thermal conductivity decreases significantly (less than 0.2W / mK), and the difference between the 55°C thermal wear resistance and the room temperature wear resistance increases significantly (greater than 28mm 3 ), and the tensile strength and tear strength dropped significantly, indicating that the thermal wear resistance and fatigue resistance under dynamic motion are extremely poor, which cannot meet the performance requirements of consumers for high-intensity sports scenes.

[0053] It can be seen from the above embodiments that the present invention provides a phase change rubber sole with low heat generation and fatigue resistance. By adopting four types of rubbers such as high vinyl polybutadiene rubber with low heat generation, carboxyl soluble butadiene rubber, trans-1,4-polyisoprene rubber, and methyl methacrylate grafted natural rubber, and matching them with a double-capsule multifunctional nano-microcapsule phase change material and a functional reinforcing agent carboxyl nano-silica, a strong chemical bond and excellent compatibility are formed between the nano-microcapsule phase change material, the reinforcing agent, and the rubber matrix, which effectively reduces the friction heat and interfacial thermal resistance between the components, and is conducive to maintaining low heat generation and high thermal conductivity. The experimental results show that the low heat generation and fatigue resistance phase change rubber sole prepared by the present invention has a compression fatigue heat generation of ≤15°C, a thermal conductivity of ≥0.6 (W / mK), and a DIN wear resistance (normal temperature) of ≤60mm 3 , DIN heat wear resistance (55℃) ≤80mm 3 , density 1.1~1.2g / cm 3 , hardness 55~65A, tensile strength ≥20MPa, right-angle tear strength ≥30 N / mm, dynamic anti-slip ≥0.6 and other excellent rubber soles. The heat generation value is ≤15℃, and the difference between the heat wear resistance at 55℃ and the DIN wear resistance at room temperature is less than 19mm 3 , compared with the existing low heat generation rubber, it has a significant breakthrough in data.

[0054] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A low heat generation and fatigue resistant phase change rubber sole, comprising the following raw materials in parts by mass: 40-50 parts of high vinyl polybutadiene rubber, 10-20 parts of carboxyl soluble styrene butadiene rubber, 10-20 parts of trans-1,4-polyisoprene rubber, 20-30 parts of methyl methacrylate grafted natural rubber, 5-10 parts of nano double capsule microcapsule phase change material, 25-35 parts of carboxyl nano white carbon black, 2-4 parts of hydrogenated petroleum resin, 3-5 parts of softening oil, 2-3.5 parts of vulcanization activator, 1.5-2.5 parts of polyethylene glycol, 2-3 parts of hydroxy silane coupling agent, 0.5-1.0 parts of stearic acid, 0.4-0.8 parts of antioxidant, 0.5-1.0 parts of antioxidant, 1.5-2.5 parts of microcrystalline wax, 0.5-1 parts of nano alumina, 2-2.5 parts of sulfur, 1-1.5 parts of accelerator DM, 0.5-0.8 parts of accelerator D and accelerator TS 0.05~0.1 portion.

2. The low heat build-up and fatigue-resistant phase change rubber sole according to claim 1, characterized in that: The high vinyl polybutadiene rubber has a vinyl content of 65-75% by mass and a Mooney viscosity of 55±5 (ML1+4@100°C).

3. The low heat build-up and fatigue-resistant phase change rubber sole according to claim 1, characterized in that: The carboxyl solution-polymerized styrene-butadiene rubber has a carboxyl molar content of 5-10%, a styrene content of 20-30%, and a Mooney viscosity of 45±5 (ML1+4@100°C).

4. The low heat build-up and fatigue-resistant phase change rubber sole according to claim 1, characterized in that: The trans molar content of trans-1,4-polyisoprene rubber is ≥90%, and the Mooney viscosity is 75±5 (ML1+4@100℃).

5. The low heat build-up and fatigue-resistant phase change rubber sole according to claim 1, characterized in that: The methyl methacrylate grafted natural rubber has a methyl methacrylate molar content of 10-15% and a Mooney viscosity of 80±5 (ML1+4@100°C).

6. The low heat build-up and fatigue-resistant phase change rubber sole according to claim 1, characterized in that: The particle size of the nano double-capsule microcapsule phase change material is 200-500nm, the phase change temperature is 28±2°C, the thermal conductivity is 1.5-3 w / (mK), and the endothermic enthalpy value is 170±20 J / g.

7. The low heat build-up and fatigue-resistant phase change rubber sole according to claim 1, characterized in that: The hydrogenated petroleum resin is selected from one or more of hydrogenated C5 petroleum resin, hydrogenated C9 petroleum resin and hydrogenated cyclopentadiene petroleum resin; The softening oil is selected from paraffin oil and / or naphthenic oil; The vulcanization activator is selected from a compound of active zinc oxide and zinc stearate; The molecular weight of the polyethylene glycol is 3600-4200; The hydroxy silane coupling agent is cyclohexylaminopropyltrimethoxysilane; The antioxidant is an amine antioxidant and / or a phenolic antioxidant; The antioxidant is selected from phosphite antioxidants and / or phenol antioxidants; The microcrystalline wax is selected from C25-C30 microcrystalline wax; The particle size of the nano-alumina is 20-50 nm, and the specific surface area is ≥230 m 2 / g.

8. The low heat build-up and fatigue-resistant phase change rubber sole according to claim 1, characterized in that: The low heat generation and fatigue resistance phase change rubber sole has a compression fatigue heat generation of ≤15°C, a thermal conductivity of ≥0.6 (W / mK), and a DIN wear resistance of ≤60mm at room temperature. 3 , DIN thermal wear resistance ≤80mm at 55℃ 3 .

9. A method for preparing the low heat build-up and fatigue-resistant phase change rubber sole according to any one of claims 1 to 8, comprising the following steps: a) Mix high vinyl polybutadiene rubber, carboxyl soluble styrene butadiene rubber, trans-1,4-polyisoprene rubber, methyl methacrylate grafted natural rubber, nano double capsule microcapsule phase change material, hydrogenated petroleum resin, softening oil, carboxyl nano white carbon black, and hydroxy silane coupling agent, knead, heat to 100-120°C, and pour out the rubber material; b) Sheeting the rubber material into a sheet with a thickness of 1±0.2 cm and leaving it for 5 to 8 hours; c) Mix the rubber sheet after storage with the additives except accelerator and sulfur, heat it to 100-120℃, and pour out the rubber; d) After rolling the rubber material for 5 to 10 times, add accelerator DM, accelerator D, accelerator TS and sulfur, and sheet out to a thickness of 0.5±0.1 cm; e) vulcanizing the 0.5±0.1 cm thick sheet to obtain a low heat buildup and fatigue resistant phase change rubber sole.

10. The preparation method according to claim 9, characterized in that: The mixing time in step a) and step c) is 8 to 10 minutes; In step e), the vulcanization temperature is 163±3°C and the time is 280±20s.

Citation Information

Patent Citations

  • Method for preparing low-heat-generation fatigue-resistant vulcanized rubber

    CN101519510A

  • Rubber composition of low heat-generating tread and tire tread using rubber composition

    CN106633258A

  • Rubber composition used for manufacturing undersoles of rubber shoes and preparation method thereof

    CN106700157A

  • High-fatigue-resistance rubber composition for tires as well as preparation method and application of high-fatigue-resistance rubber composition

    CN114854110A

  • Tire body rubber material for full run-flat tire as well as preparation method and application of tire body rubber material

    CN115505179A